2021
DOI: 10.3389/fpsyt.2020.609579
|View full text |Cite
|
Sign up to set email alerts
|

Death Associated With Coronavirus (COVID-19) Infection in Individuals With Severe Mental Disorders in Sweden During the Early Months of the Outbreak—An Exploratory Cross-Sectional Analysis of a Population-Based Register Study

Abstract: Background: Individuals with severe mental disorder (SMD) have a higher risk of somatic comorbidity and mortality than the rest of the population. We set up a population-based study to assess whether individuals with SMD had a higher risk of death associated with a COVID-19 infection (COVID-19 associated death) than individuals without SMD.Methods: Exploratory analysis with a cross-sectional design in the framework of a population-based register study covering the entire Swedish population. The Swedish Board f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 59 publications
2
30
1
2
Order By: Relevance
“…Ten studies included in the systematic review were excluded from the meta-analysis: four reported overlapping samples; 23,40,42,43 two had no meta-analysable data; 19,20 three did not differentiate between death, hospitalisation, or ICU admission; 41,44,45 and one included a control group with unknown SARS-CoV-2 infection status 18 When stratifying mortality risk by psychiatric disorder type, the most robust associations were found for psychotic and mood disorders (figure 3; appendix 4 pp 27-30). Substance use disorders and intellectual disabilities and developmental disorders were associated with higher mortality only in crude estimates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies included in the systematic review were excluded from the meta-analysis: four reported overlapping samples; 23,40,42,43 two had no meta-analysable data; 19,20 three did not differentiate between death, hospitalisation, or ICU admission; 41,44,45 and one included a control group with unknown SARS-CoV-2 infection status 18 When stratifying mortality risk by psychiatric disorder type, the most robust associations were found for psychotic and mood disorders (figure 3; appendix 4 pp 27-30). Substance use disorders and intellectual disabilities and developmental disorders were associated with higher mortality only in crude estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 841 studies, 33 of which met the inclusion criteria for the systematic review ( figure 1 , Table 1 , Table 2 ; appendix 4 pp 14–20 ), 4 , 7 , 8 , 9 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 including data from 22 countries ( Table 1 , Table 2 ) with outcomes registered between Dec 1, 2019, and Nov 30, 2020.
Figure 1 Study selection *A full list of studies excluded after full-text screening is included in appendix 4 (pp 49–51 ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three large cohort studies have indicated an approximately two-fold increased risk of mortality. 1 3 It remains unclear whether this increased risk is due to the infection itself or due to a more adverse clinical course once infected. 1 Despite this higher mortality risk, individuals with SMD have been prioritised for vaccinations in only very few countries.…”
Section: Introductionmentioning
confidence: 99%
“…Im Gegensatz dazu fand eine ähnliche Untersuchung in Südkorea[123] kein erhöhtes Infektionsrisiko von Personen mit psychiatrischen Erkrankungen und nur ein gering erhöhtes Risiko (OR 1,27) für einen schweren Krankheitsverlauf.Auch eine schwedische Registerstudie (die gesamte Bevölkerung mit rund 8 Millionen Einwohner umfassend) fand eine erhöhte Mortalität bei Personen, die an Psychosen und bipolaren Störungen litten, mit einer OR von 2, die in höherem Alter (60-79a) auf 4 anstieg. Komorbiditäten konnten den Unterschied nicht erklären[124]. Eine Kohortenstudie aus New York (N = 7348) an Patienten mit bestätigter COVID-19 Diagnose fand im Vergleich mit Patien-Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen.…”
unclassified